2019
DOI: 10.1016/j.jbiotec.2019.01.006
|View full text |Cite
|
Sign up to set email alerts
|

N-Alkyl-α-amino acids in Nature and their biocatalytic preparation

Abstract: The N-alkyl amino acid moiety is widespread in Nature.  A number of commercial products related to health contain the N-alkylated amino acid moiety.  Biocatalysis can provide more efficient and sustainable methods of accessing the N-alkyl amino acid moiety than traditional methods.  Several new enzyme classes comprising N-methyl transferases and dehydrogenases can be used for the synthesis of N-alkyl amino acids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 87 publications
(90 reference statements)
0
26
0
Order By: Relevance
“…Biosynthesis of N-alkylated amino acids can be catalyzed by other enzymes besides N-methyltransferases. However, while reductive amination using free ammonia is known for many enzymes, only few enzyme classes accept alkyl amines for N-alkylation, e.g., opine dehydrogenases, N-methyl amino acid dehydrogenases, ketimine reductases, pyrroline-5-carboxylate reductases, or imine reductases [12]. These processes differ regarding the substrate spectra of the involved enzymes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Biosynthesis of N-alkylated amino acids can be catalyzed by other enzymes besides N-methyltransferases. However, while reductive amination using free ammonia is known for many enzymes, only few enzyme classes accept alkyl amines for N-alkylation, e.g., opine dehydrogenases, N-methyl amino acid dehydrogenases, ketimine reductases, pyrroline-5-carboxylate reductases, or imine reductases [12]. These processes differ regarding the substrate spectra of the involved enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…These processes differ regarding the substrate spectra of the involved enzymes. For example, anthranilate N-methylation described here as well as N-methylglutamate production established in Pseudomonas putida using N-methylglutamate synthase and γ-glutamylmethylamide synthetase of the methylamine assimilation pathway of Methylobacterium extorquens [13] have narrow substrate spectra (e.g., GMAS from Methylovorus mays also forms γ-glutamylethylamide, also known as theanine [69]) compared with N-alkylation using the imine reductase DpkA of Pseudomonas putida [12]. Several methylated or ethylated amino acids could be produced by C. glutamicum using the wild-type or a mutant version of DpkA and either MMA or ethylamine as substrates [14,34,35].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other enzyme families catalysing a formal reductive amination such as N‐methylamino acid dehydrogenases (NMAADHs), ketimine reductases (KIREDs) and fungal Δ 1 ‐pyrroline‐5‐carboxylate reductases (P5CR) have come recently to our attention . We have, therefore, constructed a panel of enzymes and shown that one can significantly enhance amine tolerance, allowing access to a considerably broader product scope, with excellent stereospecificities, in addition to demonstrating the competencies of additional enzymes to more fully address this area (Scheme ) …”
Section: Emerging Reaction Classesmentioning
confidence: 99%